An unusual case of hyperparathyroidism, presenting as multiple skeletal lesions - Nitin Gupta; Ankur Pruthi; Ritu Verma; Anisha Manocha (World Journal of Nuclear Medicine)
We report the case of a 43-year-old male patient, who presented with severe osteoporosis and pain at multiple sites and a chest X-ray suggestive of few cystic lesions in bilateral ribs. Subsequently, the patient was referred for bone scan, in view of the suspicion of polyostotic fibrous dysplasia or neoplastic lesions. Bone scan showed homogenously increased tracer uptake in the axial and appendicular skeletal system, suggestive of metabolic superscan. Computed tomography neck localized right inferior parathyroid adenoma and expansile lytic skeletal lesions suggestive of brown tumors were also seen. This case highlights the importance of bone scan, helping in the differential diagnosis of multiple skeletal lesions.